AB0495 SERUM HIGH MOBILITY GROUP BOX-1 LEVEL IN PATIENTS WITH BEHCET'S SYNDROME AND ITS RELATIONSHIP WITH DISEASE ACTIVITY AND CLINICAL FEATURES. (2nd June 2020) - Donmez, D.; Keleşoğlu, B.; Karahan, Z. C.; Sezer, S.; Yayla, M. E.; Torgutalp, M.; Aydemir Gülöksüz, E. G.; Kinikli, G.; Turgay, T. M.; Ates, A.
Abstract : Background: Behcet's Syndrome (BS) is a chronic, multisystemic inflammatory disease. High Mobility Group Box-1 (HMGB-1) is a nuclear protein and acts as a proinflammatory molecule. The serum HMGB-1 levels were found high in various chronic inflammatory diseases. Objectives: In this cross-sectional study, serum HMGB-1 levels in patients with BS and healthy controls were studied. Also, its association with disease activity scores and clinical findings in BS were evaluated. Methods: Between March 2018 and March 2019, 90 BS patients and 50 age-sex matched healthy controls were included. Disease activity scores were assessed by using Behcet Disease Current Activity Form (BDCAF) and Behcet Syndrome Activity Score (BSAS). A p-value of <0.05 was considered to be statistically significant. Results: The demographic and clinical features were summarized in Table 1 . Serum HMGB-1 levels were significantly higher in BS than those in control group.(Table 1 ) The statistically significant corelation of serum HMGB-1 level with current clinical findings was found only in patients having eryhtema nodosum and genital ulcers in the last 1 month. The eye, central nervous system (CNS), gastrointestinal system (GIS), arterial and venous involvements were classified together as major organ involvement (MOI) (n=47). The serum HMGB-1 level was higher in patients with MOI compared to patients without MOI; however, it was not statistically significant.(40.5pg/mL and 37.2 pg/mL, p=0.560) BDCAF and BSAS scores were positively corelated with serum HMGB-1 level (p=0.022, p=0.026 respectively). (Table 2 ) Conclusion: The two studies evaluating the relationship between serum HMGB-1 level and disease activity in BS found higher levels of serum HMGB-1 level in BS than in healthy controls as in our study 1, 2 . This result supports the importance of HMGB-1 in the development of BS through its role in inflammation. De Souza et al. found no association between BDCAF and serum HMGB-1 level; whereas, we found a positive correlation with both BDCAF and BSAS 2 . This suggests that HMGB-1 can be used as a new disease activity parameter in BS. In conclusion, this study is unique as it involves the largest number of BS patients and uses BDCAF and BSAS together to assess disease activity References: [1]Ahn, J.K., et al., Extracellular high-mobility group box 1 is increased in patients with Behcet's disease with intestinal involvement. Journal of Korean medical science, 2011. 26(5): p. 697-700. [2]de Souza, A.W., et al., High mobility group box 1 serum levels are increased in Behcet's disease, but not associated with disease activity or disease manifestations. Rheumatology, 2015. 54(12): p. 2151-2155. Disclosure of Interests: None declared